ASOSIASI CENDAWAN ANTAGONIS TRICHODERMA HARZIANUM RIFAI DAN CENDAWAN MIKORIZA ARBUSKULAR UNTUK MENGENDALIKAN PENYAKIT BUSUK PANGKAL BATANG PADA KEDELAI - Latifah . .; Hendrival . .; Mihram . . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
Association of antagonistic fungi Trichoderma harzianum Rifai and arbuscular mycorrhizal fungi for controlling the stem rot disease on soybean. The research objective was to study effect of application Trichoderma harzianum and arbuscular mycorrhizal fungi (AMF) in controling stem rot disease caused by Sclerotium rolfsii Sacc on soybean. The research conducted in a Randomized Block Design (RBD) with five treatment levels: (1) without T. harzianum, without AMF, and without S. rolfsii [negative control (C-)], (2) without T. harzianum, without AMF, and S. rolfsii [positive control (C +)], (3) T. harzianum + S. rolfsii; (4) AMF + S. rolfsii, and (5) T. harzianum + AMF + S. rolfsii. Parameters observed were basal stem rot disease development and yield components. The results showed that the application of a mixture of T. harzianum and AMF caused a longer disease incubation period (8.29 days) and the severity of stem base rot disease was 11.67% number of pods per plant (62.53 pods), the number of seeds per plant (225.05 seeds), and the weight of seeds per plant (27.73 g) were higher than that of the application of T. harzianum and AMF separately.